Strategi Pengembangan Desa Wisata melalui Penguatan Kelembagaan: Studi Kasus Danau Tangkas - Dwi Hastuti; Parmadi; Junaidi; Haryadi; Siti Hodijah; Heriberta (WIDA Publishing, 2023)
This article discusses the implementation of community service (tridharma) related to the institutional strengthening strategy in the development of Danau Tangkas tourism in Tanjung Lanjut Village. Data collection methods include literature review, interviews, observations, and Focus Group Discussions (FGD). Based on the analysis of internal and external factors (SWOT) in the model of tourism attraction development to support Danau Tangkas tourism, the focus is on integrated regulatory and supervisory systems, infrastructure improvement, institutional strengthening, human resource development, and tourism marketing and promotion. Institutional strengthening through the establishment of Village-Owned Enterprises (BUMDes) involving the community aims to improve tourism facilities and add new ones, thus enhancing the appeal to tourists and positively impacting the local economy. Additionally, increasing the awareness of the local community about the potential of Danau Tangkas Tourism Village is expected to optimize the tourism potential further.